Genes, Brain, and Development : the Neurocognition of Genetic Disorders - Barnes, Marcia A., 1958- (Series for the International Neuropsychological Society., 2010)
"Genetic disorders that affect neurodevelopment are informative for understanding the relations between genes, brain, and behavior and for testing cognitive models. The chapters in the first section of this volume deal with three major neurogenetic disorders, fragile X diagnosed through its genotype often as a consequence of developmental delays, spina bifida identified in utero or at birth based on its physical phenotype - the spinal lesion, and autism, diagnosed through its behavioral phenotype in childhood, increasingly in the early preschool years"--Provided by publisher.